Lutte nationale ou fondation étatique ? - Dyala Hamzah (Revue des Mondes Musulmans et de la Méditerranée)
Is today’s recentering of the Palestinian “intellectual field” around NGO-activism and at the expense of a (muted) marxist rearguard imputable to political as well as social islamist militancy ? Why has the hegemonic presence of “Islam” in the Palestinian “public sphere”, not generated “new Muslim intellectuals”, whose exegetic commitment on the global scene does not preclude national and secular commitments ? Is it because the Palestinian “civil society” has been hindered, since the breakout of the second Intifada, by the disintegration of those infrastructures and institutions granted by the Oslo process and forced into emergency-driven actions—making it difficult for more autonomous discourses, of whatever tendency, to emerge ? This paper approaches these questions by deconstructing, in the Palestinian case, the prerequisits of an intellectual sphere; by delineating the structural constraints under which these actors labour; last, by illustrating their polarisation in the debate over suicide operations.